Preoperative Venovenous ECMO in an Infant With Late Diagnosis of Hypoplastic Left Heart Syndrome. Issue 4 (July 2020) - Eschenbach, Lena K.; Kasnar-Samprec, Jelena; Ackermann, Kilian; Schreiber, Christian; Lange, Rudiger; Cleuziou, Julie
Late diagnosis and late referral for the Norwood stage 1 procedure in patients with hypoplastic left heart syndrome is rare and associated with a higher mortality. We present a case of a cyanotic almost five-week-old infant with hypoplastic left heart syndrome, highly restrictive foramen ovale, and patent ductus arteriosus, who was bridged with venovenous extracorporeal membrane oxygenation to the Norwood stage 1 procedure.